PERLINDUNGAN HUKUM TERHADAP PEREMPUAN SEBAGAI PELAKU KEJAHATAN DALAM PROSES PENYIDIKAN DI POLRESTA DI SAMARINDA - Ika Annisa Yasmine (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACTION               In the case of criminal acts committed by women, they have legal protection at the investigation level regarding the rights of suspects based on the provisions contained in the Criminal Procedure Code (Criminal Procedure Code) which is made as a form of human rights protection for women perpetrators of crime.               For female crime investigation there are special treatment regarding reproduction function such as breastfeeding rights, checking of pregnancy, separated from male detainee and woman suspect handled by Women and Child Protection Unit (PPA) having special officer handling case of woman and child.               Based on the research results of the writer at the Resort Police Station of Samarinda City in accordance with the explanation of Bripda Bunga Tri Yulitasari as the Head of PPA Unit (Protection of Women and Children) obtained information that the factors that cause women to commit crime are Factors Fulfilling the Need, Environmental Factors, Lack of Jobs, Poverty Factors and Lack of Education Factors.Samarinda City Police Station (Polresta) to provide legal protection against women as perpetrators of criminal acts by giving rights such as Right of Completion of the Case immediately, Right to Prepare Defense, Right of Information with Free, Right to Obtain Interpreter, Right for Legal Assistance, the Right to Self-Defense of Legal Counsel, Right to Free Legal Aid, Right to Contact the Legal Counsel, Visit Rights by Personal Doctor, Right to Contact and Visit, Right to Sending Letters, Right to Receive Spiritual Visits, Right to Be Trial at Open Session to the General, the right to file a de charge a witness and an expert witness, the right to be burdened with the provision of evidentiary, the right to compensation and rehabilitation, the right of appeal and appeal, the right of judgment which has permanent strength.               Given the shortcomings provided by the Resort Police of Samarinda City against the legal protection of criminal offenses, the authors conclude that based on interviews with the Head of Unit PPA is the need for socialization, psychological enlightenment, recitations, lectures, spirituality in order not to commit crimes and the need for police to reform the process of investigation by improving the professionalism of the investigation and the need for positive cooperation between the public, the government and the police in enhancing knowledge in the field of law concerning protection of women. Keywords: Protection Officers, Women, Crime